Pengaruh Word Of Mouth, Destination Image, Destination Branding Terhadap Minat Berkunjung Di Jatim Park 3 Kota Batu Malang (Studi Kasus Mahasiswa FEB Unisma Angkatan tahun 2019/2020) - Ulfa Uswatul Hasanah; Nur Hidayati; M. Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to analiyze the direct influence andi ndirect influence of the three variables, namely Word of Mouth, Destination Image, Destination Branding on the interest of visiting the east java Park 3 Batu Malang. This type of research uses the type survey research. This research was conducted by distributing questionnaires to Students of the Faculty of Economics and Business UNISMA Force 2019-2020 with a total of 90 respondents. The analysis technique used in this research is multiple linier regression analysis. Based on the results of the analysis conducted showed the value of t arithmetic(6,112)> t table (1,987) and with a significance level of 0,000<0.005 so that word of mouth has a positive effect on interest in visiting. Based on the result of the analysis carried out shows that the value of t arithmetic(5,774)>table (1,987) and with a significant level of 0.000<0.005 so the destination image has a positive effect on interest in visiting the 3 stone city of east java. Based on the result of the analysis carried out shows that the value of t arithmetic(5,774)>table (1,987) and with a significant level of 0.000<0.005 so the destination branding has a positive effect on interest in visiting the 3 stone city of east java. Keyword: Word Of Mouth, Destination Image and Dation Branding